3,5-Diethoxy-3’-hydroxyresveratrol (DEHR) ameliorates liver fibrosis via caveolin-1 activation in hepatic stellate cells and in a mouse model of bile duct ligation injury - Lee, Phil Jun; Park, Hye Jin; Cho, Namki; Kim, Hong Pyo (Molecules, 2018)
Hepatic stellate cells (HSCs) are involved in the pathogenesis of liver fibrosis. Resveratrol, 3,5,4’-trihydroxystilbene, is a dietary polyphenol found in natural food products. Here, we evaluated the anti-proliferative effects of a synthetic resveratrol derivative, 3,5-diethoxy-3’-hydroxyresveratrol (DEHR), on HSCs. Flow cytometry and Western blot analyses showed that DEHR induces apoptosis through the upregulation of cleaved caspase-3 and poly (ADP-ribose) polymerase expression and reduction in the level of an anti-apoptotic protein B-cell lymphoma 2 (Bcl2). As caveolin-1 (CAV1), a competitive inhibitor of heme oxygenase 1 (HO-1), is related to apoptotic proteins in hepatic cells, we focused on the role of CAV1 in DEHR-induced apoptosis in HSCs through Western blot analyses. Our results showed that the inhibitory effect of DEHR on cell viability was stronger in HO-1 siRNA-transfected cells but weakened in CAV1 siRNA-transfected cells. Collagen concentration was significantly reduced, whereas CAV1 expression increased after treatment of a bile duct ligation injury-induced liver fibrosis model with DEHR for four weeks. We confirmed that DEHR treatment significantly reduced fibrous hyperplasia around the central veins, using hematoxylin and eosin and Sirius red staining. DEHR ameliorates liver fibrosis in vitro and in vivo, possibly through a mechanism involving CAV1.
Keywords: Animals; Apoptosis; Bile Ducts; Caveolin 1; Collagen; Disease Models, Animal; Gene Expression Regulation; Heme Oxygenase-1; Hepatic Stellate Cells; Humans; Ligation; Liver; Liver Cirrhosis; Membrane Proteins; Mice; Resveratrol; Signal Transduction; Transcriptional Activation; 3,5-Diethoxy-3’-hydroxyresveratrol (DEHR); Caveolin-1 (CAV1); Heme oxygenase 1 (HO-1); Hepatic stellate cell (HSC)